2008
DOI: 10.5210/fm.v13i10.2238
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for the non-adoption of OpenOffice.org in a data-intensive public administration

Abstract: Several academic studies have already been conducted to investigate the reasons influencing the adoption of open source desktop software such as Linux and OpenOffice.org. However, few studies have been devoted to determine the reasons for not adopting open source desktop software. In order to address this issue, we present a case study on the Belgian Federal Public Service (FPS) Economy which considered the use of OpenOffice.org, but eventually decided not to adopt OpenOffice.org as their primary office suite.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 0 publications
0
25
0
1
Order By: Relevance
“…[9, p. 42]. For example, it has been shown that even in the presence of several strong arguments in favor of the adoption of OSS, the existence of additional factors with a negative impact on adoption may result in non-adoption [13]. Previous studies that investigate the barriers to the adoption of OSS generally use a sample of organizations that have not adopted OSS (e.g., [10,11,13]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9, p. 42]. For example, it has been shown that even in the presence of several strong arguments in favor of the adoption of OSS, the existence of additional factors with a negative impact on adoption may result in non-adoption [13]. Previous studies that investigate the barriers to the adoption of OSS generally use a sample of organizations that have not adopted OSS (e.g., [10,11,13]).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, these studies consider both organizations with a low extent of adoption and organizations with a high extent of adoption. A second line of studies has investigated the non-adoption of OSS (see e.g., [20,12,5,13,19,10,11]). These studies are concerned with determining which barriers prevent organizations from adopting OSS.…”
Section: Introductionmentioning
confidence: 99%
“…Over time, the organization may build up the required expertise internally, which makes the use of external support obsolete. We observed the desire to provide support for OSS internally in a number of our case studies [7,14].…”
Section: Relationship With Assimilation Stagementioning
confidence: 99%
“…There is, however, a notable lag in OSS adoption compared to their proprietary counterparts in domains such as client operating systems and office productivity software which is a clear indicator that there may be significant barriers to OSS adoption among some sectors of the user population (Nagy, Yasssin, & Bhattacherjee, 2010). Although, there is a general consensus among the majority of researchers that usability is one of the main hindrances to OSS adoption, as discussed by Sen (2007b) and Nichols and Twidale (2003), some studies conducted suggest that usability is not really the main issue (Huysmans, Ven, & Verelst, 2008). The study Huysmans et al (2008), conducted concluded that, the main issue was migration of the data from PS to OSS especially in advanced and data intensive organizations.…”
Section: Introductionmentioning
confidence: 99%
“…Although, there is a general consensus among the majority of researchers that usability is one of the main hindrances to OSS adoption, as discussed by Sen (2007b) and Nichols and Twidale (2003), some studies conducted suggest that usability is not really the main issue (Huysmans, Ven, & Verelst, 2008). The study Huysmans et al (2008), conducted concluded that, the main issue was migration of the data from PS to OSS especially in advanced and data intensive organizations.…”
Section: Introductionmentioning
confidence: 99%